(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The present study was carried out to assess the quality and quantity with the study of the antibacterial activity of phytochemicals present in the methanolic and aqueous extract of leaves and roots of the plane Glycyrrhiza glabra L. growth in Algeria. The phytochemicals detected were flavonoids, glycoside, tannins, saponin, terpenoids and Steroids. The quantitative analyses showed that leaves methanolic extract had the highest total phenolics content (TPC: 650,652 mg GEA/g), total flavonoids content (TFC: 184,023 mg QE/g) and total tannins content (TTC: 5.8 mg GAE/g). But roots methanolic extract had the highest total saponins content (TSC:191,183mg DE/g). Also These extracts were tested in vitro against some gram positive bacterial strains such as Staphylococcus aureus ATCC 25923 and gram negative such as Escherichia coli (ATCC25922) Pseudomonas aeruginosa (ATCC 27853), Salmonella typhimurium (ATTC 13311), using the diffusion method in agar (antibiogram). Methanolic and aqueous extract of the leaves and roots have shown considerable activity against most organisms tested, leaves methanolic and aqueous extract showed a high activity at a concentration of 100mg/ml compared to roots methanolic and aqueous extract at the same concentration, especially against Gram+ strains. The diameters of inhibition zones ranged from 7 to 22 mm for all treatments. The values of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined. And the CMB/CMI report made it possible to specify the mode of action of the substance. It was observed that the CMB / CMI of crude methanol extracted from the leaves and roots Glycyrrhiza glabra L. reached 2 , with the bacterial strain Escherichia coli (ATCC25922) it means has a bactéricidal effect. The methanolic extract of Glycyrrhiza glabra L. roots provided the highest antioxidant activity against free radical inhibition of DPPH. The results obtained in this study and the comparison with other works in the same field, allowed us to reveal the importance attributed by traditional medicine to Glycyrrhiza glabra L. as a source of natural antiseptics.